Academic self-efficacy as a predictor toward decisional procrastination among college students preparing a thesis in Indonesia - THOYYIBATUS SARIRAH; SAPUTRI ARIFSA CHAQ (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this study was to examine the relationship between college students’ sense of academic self-efficacy and their tendency to put off making important decisions while working on their thesis.Method: With the help of a sampling strategy, we collected responses from 120 college students. Both the Academic Self-Efficacy Scale and the Melbourne Decision-Making Questionnaire were used. During the evaluation, researchers used SPSS 22.0.Findings: The data analysis using simple regression found that academic self-efficacy significantly influenced decisional procrastination toward college students preparing a thesis. Students’ decisional procrastination was negatively correlated with their academic self-efficacy, such that higher levels of academic self-efficacy were associated with lower levels of procrastination in thesis preparation.Implications/Novel Contribution: The findings of this study have important implications for the field of education because they shed light on how factors such as students’ levels of self-confidence or their perceptions of the tasks they were assigned can affect their performance. Individual differences and the types of tasks that influenced procrastination could be investigated further in studies that examine demographic factors.